METHOD OF DETECTION OF RESIDUAL TISSUES IN RECURRENT OPERATIONS ON THE THYROID GLAND - A. V. Gostimskiy; A. F. Romanchishen; I. V. Zaitseva; Yu. V. Kuznetsova (Вестник хирургии имени И.И. Грекова)
A search of residual tissues is complicated in recurrent operations on the thyroid gland. The Saint-Petersburg Centre of Surgery of the Endocrine System and Oncology developed the method of detection of residual tissues of the thyroid gland with the aim of preoperative chromothyroidolymphography under control of ultrasound. The method consisted of US performance during 15-20 minutes before the operation and an introduction of 1% sterile water solution of methylene blue in revealed residual tissues of the thyroid gland. The volume of injected coloring agent was 0,5-2 ml in the residual tissue volume smaller than 9 cm³ and 2-3 ml injected in case of more than 9 cm³. The residual tissues of the thyroid gland accurately visualized during the following operation. Described method gives the possibility to detect all regions of residual tissues which should be removed and at the same time it shortens a revision and surgery trauma.